Microbiome and pediatric leukemia, diabetes, and allergies: Systematic review and meta-analysis. - Rachel Gallant; Samiha Reza; Joseph L Wiemels; Mel Greaves (PLoS ONE)
Background Despite the different pathologies and genetic susceptibilities of childhood ALL, T1DM and allergies, these conditions share epidemiological risk factors related to timing of infectious exposures and acquisition of the gut microbiome in infancy. We have assessed whether lower microbiome diversity (Shannon Index) and shared genus/species profiles are associated with pediatric ALL, allergies, and T1DM. Methods and findings Literature search was performed using PubMed, Embase, Cochrane, and Web of Science databases. Case-control, meta-analyses, and cohort studies were considered for inclusion. Inclusion criteria: (i) subjects age 1-18 years at diagnosis, (ii) reports effect of microbiome measured prior to/at time of diagnosis/first intervention (iii) outcome of ALL, allergies, asthma, or T1DM, (iv) English text. Exclusion criteria: (i) age < 1 or >18 years at diagnosis, (ii) Down Syndrome-associated ALL, (iii) non-English text, (iv) reviews, pre-print, or abstracts, (v) heavily biased studies. Abstract and full text screening were performed by two independent reviewers. Data extraction was performed by one reviewer following PRISMA guidelines. Data were pooled using a random-effects model. Eighty-eight studies were included in the analysis, with seventy-seven in the qualitative analysis and 54 in the meta-analysis. Cases were found to have lower alpha-diversity than controls in ALL (SMD:-0.78, 95%CI:-1.21, -0.34), T1DM (SMD:-1.26, 95%CI:-3.49, 0.96), eczema (SMD:-0.34, 95%CI:-0.56, -0.12), atopy (SMD:-0.06, 95%CI:-0.34, 0.22), asthma (SMD:-0.37, 95%CI:-1.16, 0.42), and food allergy (SMD:-0.11, 95%CI:-0.63, 0.41). Conclusions These results highlight similarities in the microbiome diversity and composition of children with ALL, T1DM, and allergies. This is compatible with a common risk factor related to immune priming in infancy and highlights the gut microbiome as a potentially modifiable risk factor and preventative strategy for these childhood diseases.